Analysis of determinants of hydration status of medical students at the Universitas Sumatera Utara - Nenni Dwi Aprianti Lubis; Ridwan Balatif; Isni Dhiyah Almira (AcTion: Aceh Nutrition Journal, 2023)
Dehydration can impair the operation of the body's organs and cause mortality because the human body is 60% water. The purpose of this study was to analyze factors related to hydration status. This study using a cross-sectional research design in a descriptive-analytical study. The study was conducted in the Nutrition Department of the Faculty of Medicine, Universitas Sumatera Utara. The study was conducted from September to October 2020.  99 students were chosen at random to participate in the study. Respondent characteristics, physical activity, nutritional status, body composition, fluid intake, and hydration status were among the information gathered. Subject follow-up was carried out for 7 consecutive days. Positive relationships and significance between dietary status (p < 0,014), total body water (p < 0,018), muscle mass (p < 0,012), level of exercise (p < 0,003), and total fluid intake (p < 0,044) were found in the results of the multiple regression test. Additionally, a negative association and significance between visceral fat (p < 0,03) and body fat (p < 0,016) is discovered. Based on the test's findings, a determination coefficient with a value of 85,5% was calculated, meaning that 85,5% of factors influencing hydration status include dietary habits, body composition, visceral fat, total body water, muscle mass, level of exercise, and total fluid intake. Conclusion, nutritional status, total body water, muscle mass, physical activity, and overall fluid intake all have a positive correlation with hydration status. However, there was shown to be a negative correlation between body fat and visceral fat and hydration status.